The methanol-ethyl acetate partitioned fraction from Chinese olive fruits inhibits cancer cell proliferation and tumor growth by promoting apoptosis through the suppression of the NF-κB signaling pathway. Issue 12 (21st November 2016) - Hsieh, Shu-Chen; Hsieh, Wang-Ju; Chiang, An-Na; Su, Nan-Wei; Yeh, Yu-Te; Liao, Yi-Chun
Abstract : The anti-proliferation and anti-tumor effects on cancer cells mediated by MEO is due to inhibition of the NF-κB pathway. Abstract : Chinese olives ( Canarium album L.) have historically been used for medicinal purposes rather than commercially for oil. In this report, we reveal that the methanol-ethyl acetate partitioned fraction from Chinese olive fruits (MEO), of which ellagic acid accounted for 12%, exhibited profound anti-proliferative activities in the human colon cancer cell line, HCT116. Additionally, oral administration of MEO remarkably inhibited the tumor growth of subcutaneously implanted CT26 cells, a mouse colon carcinoma cell line, in BALB/c mice. Treatment with MEO induced a significant increase in the percentage of apoptotic cells and resulted in poly(ADP-ribose) polymerase (PARP) cleavage, suggesting that MEO inhibits cancer cell proliferation by promoting apoptosis. Our study also showed that MEO exerted the most potent effect on the inhibition of NF-κB-mediated signaling among the partitioned fractions from Chinese olives. This process employed the use of reporter-based bio-platforms that are capable of detecting the activation of NF-κB. In addition, phosphorylation of NF-κB signaling-associated proteins, IKKα/β, IκBα, and p65, was reduced in MEO-incubated cancer cells, indicating that MEO suppresses NF-κB activation. Moreover, MEO treatment significantly suppressed lipopolysaccharide (LPS)-induced cancer cell proliferation, demonstrating that MEO promotes cancer cell apoptosis through the inhibition of the NF-κB signaling pathway. In summary, our findings demonstrate that the methanol-ethyl acetate partitioned fraction from Chinese olive fruits inhibits cancer cell proliferation and tumor growth by promoting apoptosis through the suppression of NF-κB signaling. Therefore, the Chinese olive fruit has promising potential in cancer treatment.